ICOS, SLAM and PD‐1 expression and regulation on T lymphocytes reflect the immune dysregulation in patients with HIV‐related illness with pulmonary tuberculosis - Jurado, Javier Oscar (2012)
Background: Tuberculosis (TB) continues to be the most frequent cause of illness and death from an infectious agent globally, and its interaction with HIV is having devastating effects. To investigate how HIV alters the immune response to Mycobacterium tuberculosis (Mtb), we assessed basal and Mtb-induced proliferation, cytokine production, and expression of signalling lymphocytic activation molecule (SLAM), inducible costimulator (ICOS) and programmed death-1 (PD-1) on T lymphocytes from HIV-positive individuals coinfected with TB, HIV-positive subjects, TB patients and healthy donors (HD).Findings: HIV-TB patients showed increased ICOS, SLAM and PD-1 basal levels on T lymphocytes, whereas HIV-positive individuals displayed elevated levels of SLAM and PD-1, TB patients high levels of SLAM, and HD low levels of the three proteins. Mtb-stimulation enhanced ICOS expression in the four groups, but only TB and HD increased SLAM and PD-1 levels.Conclusions: These data show the immune deregulation that takes place during the immune response against TB in different study populations.